Application techniques of pesticides in greenhouse tomato crops - Dario, Gustavo [UNESP]; Precipito, Laís Maria B. [UNESP]; de Oliveira, João Victor; Lucilhia, Leonardo Vinicius da S.; de Oliveira, Rone B. (FapUNIFESP (SciELO), 2020)
Due to the deficiency of information on application technology in horticulture, the aim of this research was to evaluate the effect of three application techniques on different parts of the tomato canopy cultivated under greenhouse. The techniques evaluated were 1= Spray gun with two hollow cone nozzles, model JA-2 (700 kPa), application rate of 618 L ha-1; 2= Vertical boom spray equipped with six nozzles, model ATR 0.5 (700 kPa), application rate of 493 L ha-1; 3= Vertical boom spray with six standard flat fan nozzles, model AXI 11002 (400 kPa), application rate of 1442 L ha-1. As application quality indicators, the relative deposit (quantitative) and the coverage (qualitative) of the tomato leaves in the internal and external collection positions of the plants, in the upper, middle and lower strata of the tomato canopy were measured. In the lower and middle canopy strata, the relative deposit was respectively 21% and 34% smaller in the internal part of the plants in relation to the external, however in the upper stratum there was no difference. On average, the coverage was 2.5 times smaller on the abaxial surface in relation to the adaxial leaf surface. The Spray gun JA-2 (618 L ha-1), used in commercial farming, provided better quality of the application. However, there is a need to optimize the application techniques in order to provide better distribution of the spray, mainly in the critical regions, such on the inside of the plants in the lower and middle canopy strata and the abaxial surface of the leaves.
Técnicas de aplicação de produtos fitossanitários no tomateiro em ambiente protegido
Keywords: Application technology; Coverage; Deposit; Solanum lycopersicum